2023
DOI: 10.3390/ani13193124
|View full text |Cite
|
Sign up to set email alerts
|

Osteology of the Hamadryas Baboon (Papio hamadryas)

Christophe Casteleyn,
Estée Wydooghe,
Jaco Bakker

Abstract: Besides living as a free-ranging primate in the horn of Africa and the Arabian Peninsula, the hamadryas baboon has an important place in zoos and can be found in biomedical research centers worldwide. To be valuable as a non-human primate laboratory model for man, its anatomy should be portrayed in detail, allowing for the correct interpretation and translation of obtained research results. Reviewing the literature on the use of the baboon in biomedical research revealed that very limited anatomical works on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…Formations of fossa hypophysialis, dorsum sellae, processus clinoideus anterior and processus clinoideus posterior and tuberculum sellae were reported in humans (Netter, 2010). In a study on monkeys, the authors reported fossa hypophysialis, dorsum sellae, processus clinoideus caudalis and processus clinoideus rostralis (Casteleyn et al, 2023). The processus clinoideus rostralis was not found in the models in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…Formations of fossa hypophysialis, dorsum sellae, processus clinoideus anterior and processus clinoideus posterior and tuberculum sellae were reported in humans (Netter, 2010). In a study on monkeys, the authors reported fossa hypophysialis, dorsum sellae, processus clinoideus caudalis and processus clinoideus rostralis (Casteleyn et al, 2023). The processus clinoideus rostralis was not found in the models in the present study.…”
Section: Discussioncontrasting
confidence: 66%